Selective flotation of fine-grained pentlandite from low grade polymetallic ore. (January 2019) - Kumar, Haresh; Luukkanen, Saija
Highlights: Investigated the effect of a new rotor-stator mechanism on selective flotation of fine grained pentlandite. Effect of impeller speed on flotation performance was investigated. As a result, Ni recovery was improved in pitched blade turbine impeller tests. Abstract: The main aim of this study is to test a new type of an impeller in selective flotation of a low grade polymetallic Ni-Cu-PGE ore. The effect of impeller type and speed on bubble size and nickel grade and recovery was investigated. It was noticed that bubble size was independent of impeller type and speeds. However, the highest volume of small bubbles was measured using a new type of impeller. The results showed that a pitched blade turbine impeller has a positive effect on nickel grade and recovery at higher impeller speed.